Effect of oral bad habit breath through the mouth with face shape in children: Pengaruh kebiasaan bernafas melalui mulut dengan bentuk wajah pada anak - Leny Sang Surya; Sri Intan Millenia; Rosa Gusmi Putri; Rahma Nadila Syari (Makassar Dental Journal, 2022)
Habit is a pattern of behavior that is repeated; in the oral cavity is also known as oral bad habit and naturally occurs at the age of less than six years. Oral habit cancontinue at the age of more than six years which can cause abnormalities in the dentofacial structure. This article discusses the influence of the habit of breathing through the mouth on the shape of the face in children. With a literature review design, articles were collected using Google Scholar, Pubmed and ScienceDirectusing the keywords oral bad habit, mouth breathing, malocclusion. The selected articles are publications in 2015-2022, research subjects are children aged 6-12years, full-text available, and written in English and Indonesian. It was concluded that oral bad habits often occur in children and even in infants. Oral bad habitsinclude thumb sucking, nail biting, lip sucking, tongue pushing, and mouth breath-ing. Oral bad habits such as mouth breathing have an influence on theoccurrence of malocclusion, especially in children who are still in the growth and development stage, namely elementary school children.